2019
DOI: 10.1002/ccd.28660
|View full text |Cite
|
Sign up to set email alerts
|

Cost of coronary syndrome treated with percutaneous coronary intervention and 30‐day unplanned readmission in the United States

Abstract: Objectives: This study aimed to examine the cost of coronary syndrome treated with percutaneous coronary intervention (PCI) and 30-day unplanned readmissions. Background: There is limited understanding of the hospital cost of index PCI and 30-day unplanned readmissions. Methods: Patients undergoing PCI between 2010 and 2014 in the U.S. Nationwide Readmission Database were included. The primary outcome was total cost defined by cost of index PCI and first unplanned readmission within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This underscores the importance of using PCI in the appropriate patient population. Of note, data from the U.S. NIS from 2010 to 2014 reported that the 30-day hospital cost of PCI is approximately USD 10.8 billion per year [82], representing a significant financial burden to the U.S. healthcare system. As a result, it is also critical to determine which patients will optimally benefit from PCI to avoid an unnecessary economic burden.…”
Section: Cad Revascularization-challenges With Access Appropriate Use...mentioning
confidence: 99%
“…This underscores the importance of using PCI in the appropriate patient population. Of note, data from the U.S. NIS from 2010 to 2014 reported that the 30-day hospital cost of PCI is approximately USD 10.8 billion per year [82], representing a significant financial burden to the U.S. healthcare system. As a result, it is also critical to determine which patients will optimally benefit from PCI to avoid an unnecessary economic burden.…”
Section: Cad Revascularization-challenges With Access Appropriate Use...mentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions, Kwok et al 1 examine the costs associated with readmission after percutaneous coronary intervention (PCI). They evaluated patients in the National Readmission Database from 2010 and 2014 and identified costs incurred within 30 days of an index PCI.…”
Section: Condition 30‐day Readmission Rate Cost Per Readmission Citationmentioning
confidence: 99%
“…1 Percutaneous coronary intervention (PCI) accounts for more than $10 billion per year in hospital costs alone. 2 While there were initial reductions in the volume of PCIs performed for stable coronary artery disease (CAD) after the publication of the Appropriate Use Criteria for Coronary Revascularization in 2009, 3 PCI rates have since then largely remained stable. 4 As such, an opportunity for intervention (pardon the pun) still exists in this domain.…”
mentioning
confidence: 99%